Short thorax and disproportionate dwarf ism due to Kniest dysplasia - Ratnaweera, D.H .; Senanayake, M.P. (My University, 2007)
A breastfed male infant aged six weeks presented with constipation and weight loss. He was the third born to a 33 year old mother in a non-consanguineous marriage. Both siblings were normal. Abnormalities observed were: short length (crown-toheel 46cm), disproportionate body proportions, short barrel shaped chest (Figure 1), a relatively large head, kyphoscoliosis, enlarged knees and elbows with limited range of active and passive movements, bilateral inguinal herniae, flat facies, prominent eyes and a wide posterior cleft palate. Cardiovascular, respiratory, abdominal and neurological examinations were normal. X rays showed vertebral clefts in thoracic spine (Figures 2 & 3), flared metaphyses and large epiphyses in femur and tibia (Figure 4). Expressed breast milk fed using a long teat corrected weight loss and constipation. Cleft palate repair was planned for nine months of age. Herniotomy was performed. On follow up at four months he had satisfactory weight gain and normal development.